Nanostructured Eu-doped Ceria for humidity sensing: A morphological perspective - Ortega, P. P. [UNESP]; Gherardi, S.; Spagnoli, E.; Fabbri, B.; Astolfi, M.; Zonta, G.; Landini, N.; Malagù, C.; Aldao, C. M.; Ponce, M. A.; Simões, A. Z. [UNESP]; Longo, E. (Elsevier, 2024)
Humidity is a ubiquitous variable with severe impacts on physical and chemical processes, thus demanding precise measuring and monitoring. As an alternative to bulky analytical instrumentations, chemoresistive gas sensors are promising candidates for humidity sensing devices. Herein, we investigated how the morphology of Eu-doped CeO2 nanostructures influenced their humidity detection. Nanostructures with spherical, rod, polyhedron, and cube morphologies were synthesized using the microwave-assisted hydrothermal method. XRD and Raman spectroscopy analyses revealed that the samples were crystalline and without secondary phases, displaying the highest level of structural disorders for nanorods. HRTEM analysis showed that the exposed facets depended on the morphology and that the most reactive surface (composed of (2 0 0) planes) was predominant in the nanorods and nanocubes. Thick films based on the nanostructures were prepared via the screen-printing technique, obtaining porous layers without discontinuities. At 55% RH, the response of the sensor based on Eu-doped Ceria nanorods was about 150% and 60% higher than of the Eu-doped nanopolyhedra and undoped nanoparticles, respectively, which was assigned to their reactive facets, higher specific surface area, and higher level of structural defects. The sensing mechanism was attributed to electronic conduction resulting from the adsorption of water molecules on the surface of the nanostructures.
Keywords: Cerium dioxide; Gas sensors; Humidity; Morphology; Nanostructures